Preparation method of gold ion adsorbent
By introducing active functional groups such as nitrogen and sulfur on chitosan to form a macromolecular network structure, the problem of competitive adsorption between gold ions and impurity metal ions in the prior art is solved, and efficient and selective gold ion adsorption is achieved, meeting the efficient recovery of gold ions in gold ore leaching liquid.
Patent Information
- Application Number
- CN202411641251.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
Smart Images

Figure BDA0005138519900000141 
Figure BDA0005138519900000151 
Figure BDA0005138519900000191
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy and relates to a method for preparing a gold ion adsorbent. Background Art
[0002] Gold (Au), as a scarce precious metal, is widely used in the fields of medicine, electronic devices, and aerospace. However, my country's gold resources are scarce, most of the gold mines are of low grade, and are usually embedded in the gangue minerals in the form of fine particles, making them extremely difficult to separate. As a limited and non-renewable resource, the recovery of gold is of great significance to improving economic benefits and achieving environmental protection.
[0003] At present, the leaching of gold ore mainly adopts hydrometallurgical process, and the commonly used methods include cyanidation, thiosulfate, bromination, iodination and thiourea. However, after leaching, gold and other impurity metals usually coexist in the leachate in the form of ions, and the concentration of gold is usually much lower than the concentration of impurity metals in the leachate. The main methods for extracting gold from the leachate include displacement, extraction and adsorption, among which adsorption is the most widely used method. Activated carbon, as a widely used adsorption material, has the advantages of simple operation and recyclability, but its adsorption capacity is limited, and the impurity metal ions in the solution are easily competitively adsorbed with gold ions, thereby reducing the recovery rate of gold ions. Therefore, it is urgent to develop a green adsorbent that has specific selectivity for gold ions, large adsorption capacity and is reusable.
[0004] Chitosan, as a renewable green material, is composed of randomly distributed deacetylated units and acetyl units. It has two main active functional groups, the amino group (-NH2) at the C2 position, which exhibits strong nucleophilicity, and the hydroxyl groups (-OH) at the C3 and C6 positions. These active functional groups not only have the ability to coordinate with metal cations, but also provide active sites for cross-linking modification with other active functional groups. Under acidic conditions, the β-1,4 glycosidic bonds of chitosan molecules will be + Under the action of protonation reaction, the stability of its chemical bond is weakened, which leads to the cleavage of glycosidic bond and the hydrolysis of chitosan molecular chain. + Protonation reaction occurs to form -NH 3+ The generation of positive charge increases the hydrophilicity of chitosan, further intensifying the hydrolysis of chitosan.
[0005] In order to improve the stability of chitosan under acidic conditions, researchers at home and abroad usually use cross-linking agents to react with the active sites of chitosan to form a complex network structure, thereby increasing the molecular weight and structural rigidity of chitosan to reduce the occurrence of its hydrolysis reaction. However, during the reaction, a large number of active sites on chitosan will be consumed, resulting in a decrease in its adsorption capacity for target ions. Therefore, it is urgent to design a gold ion adsorbent to overcome the defects of the existing technology to meet the needs of practical applications. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a gold ion adsorbent. In the present invention, the -NH2 group in the glucosamine structural unit of chitosan is connected with active functional groups such as nitrogen and sulfur through the cross-linking effect of glutaraldehyde to form a macromolecular network structure. The adsorption of gold ions can be achieved through the coordination and complexation of sulfur atoms, amine groups and gold ions and redox as well as the electrostatic adsorption of protonated groups. The polymer can be used for extracting gold ions from ore gold leaching liquid and electronic waste. The overall preparation process is simple, easy to operate and low in cost, and the obtained adsorbent has high adsorption capacity and good selectivity.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for preparing a gold ion adsorbent, the preparation method comprising:
[0009] (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution;
[0010] (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution;
[0011] (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution;
[0012] (4) subjecting the reaction solution in step (3) to solid-liquid separation, and subjecting the obtained solid particles to elution treatment, filtration treatment and drying treatment in sequence to obtain a gold ion adsorbent;
[0013] There is no particular order in which steps (1) and (2) are performed.
[0014] In the present invention, the -NH2 group in the glucosamine structural unit of chitosan is connected with active functional groups such as nitrogen and sulfur through the cross-linking effect of glutaraldehyde to form a macromolecular network structure. The adsorption of gold ions can be achieved through the coordination and complexation of sulfur atoms, amine groups and gold ions and redox as well as the electrostatic adsorption of protonated groups. The polymer can be used for extracting gold ions from ore gold leaching liquid and electronic waste. The overall preparation process is simple, easy to operate and low in cost, and the obtained adsorbent has high adsorption capacity and good selectivity.
[0015] It should be noted that the grade of chitosan powder in the present invention is that the deacetylation degree is ≥ 95% and the viscosity is 100 mPa.s to 200 mPa.s.
[0016] It should be noted that in order to solve the problem that the cross-linking reaction between the cross-linking agent and chitosan consumes a large number of active sites on chitosan, resulting in a decrease in its adsorption capacity for target ions, the present invention introduces additional active functional groups to increase the number of active sites on chitosan, thereby enhancing its adsorption performance. According to the theory of hard and soft acids and bases, soft acids (Au) are more inclined to form stable complexes with soft bases (N, S), and nitrogen atoms are located in the sp 3 The lone pair electrons in the hybrid orbital have higher energy, are easy to transfer electrons, and can provide electrons to Au through the inductive effect. 3+ The 5d orbital of the sulfur atom forms a stable coordination bond. Due to its larger atomic radius and more dispersed electron cloud, the sulfur atom has a stronger polarizability. The arc pair electrons in the 3p orbital are more easily polarized and deformed, and can bind to Au. 3+ The 5d orbitals of Au atoms overlap to form a stable Au-S bond, and the π-donation effect of sulfur atoms further enhances the stability of the Au-S bond. Through chemical modification, N-containing functional groups such as amine and amide groups and S-containing functional groups such as thiol and thioether are introduced into chitosan. These active functional groups can form stable coordination bonds (Au-N, Au-S) with the d orbitals of Au in the solution, and under the action of redox, the adsorbed Au 3+ Reduced to elemental gold, thus achieving efficient adsorption of gold ions. Therefore, using chitosan as a matrix material and introducing active functional groups containing nitrogen, sulfur and other elements provide a more promising solution for the efficient and selective recovery of precious metals in solution.
[0017] It should be noted that the present invention efficiently modifies chitosan materials through a simple emulsion polymerization method, which is easy to operate and has strong controllability. It can effectively introduce active groups under relatively mild reaction conditions and a reaction environment at a relatively low temperature, thereby improving the modification efficiency of the material and the product performance.
[0018] It should be noted that the present invention increases the active sites on chitosan by introducing active groups such as nitrogen and sulfur, thereby effectively compensating for the problem of partial active site loss caused by the cross-linking process. These introduced active groups can not only form a stable coordination bond with the d orbital of Au in the solution, but also have a certain reduction ability, and the gold ions adsorbed on the material can be reduced to elemental gold by redox reaction. This synergistic effect not only significantly improves the adsorption efficiency of chitosan-based materials for gold ions, but also achieves selective adsorption of gold ions.
[0019] It should be noted that the raw materials used in the present invention are of various types, widely available and inexpensive, thereby significantly reducing the production cost.
[0020] It should be noted that the gold ion adsorbent in the present invention is a porous spherical particle with uniform particle size and a large specific surface area, and the specific surface area range is approximately 1.0 m 2 / g~3.0m 2 / g.
[0021] It should be noted that the step of first dissolving the chitosan powder in the acetic acid solution and then adding the formaldehyde solution in the present invention is more conducive to accurately controlling the reaction conditions compared to the step of simultaneously mixing the chitosan powder, the acetic acid solution and the formaldehyde solution, so that the formaldehyde can well protect the amino groups in the chitosan from being excessively cross-linked in the subsequent reaction and reducing the adsorption capacity, making the adsorbent structure more stable, increasing the chitosan active sites, and thus improving the adsorption capacity.
[0022] As a preferred technical solution of the present invention, the ratio between the mass of the chitosan powder and the volume of the acetic acid solution is 1g:4mL~5mL, for example, it can be 1g:4mL, 1g:4.2mL, 1g:4.4mL, 1g:4.6mL, 1g:4.8mL, 1g:5mL, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The ratio between the mass of the chitosan powder and the volume of the acetic acid solution in the present invention is 1g:4mL~5mL, because within this range, the chitosan powder can be fully dissolved to form a uniform solution, which is conducive to the formation of microspheres in the preparation process. If it is not within this range, it may lead to incomplete dissolution or excessive dissolution, too high or too low viscosity, and it is difficult to form microspheres in the preparation process, which affects the structural stability of the adsorbent and thus reduces its adsorption efficiency.
[0024] Preferably, the mass concentration of the formaldehyde solution is 0.2% to 2%, for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] It should be noted that formaldehyde is used as a protective agent in the present invention to react chemically with the amino groups on the chitosan chain. The carbon atoms in the formaldehyde have a high electrophilic state, and the vacancies of the p orbitals can overlap with the arc pairs of electrons of the amino groups to form σ bonds. In this process, the electron density center distribution between the C atoms in the formaldehyde and the arc pairs of electrons of the amino groups forms a covalent bond structure, which effectively protects the active groups of chitosan, thereby significantly improving its adsorption capacity for target ions. At the same time, under the action of the cross-linking agent, a complex spatial network structure is formed, which not only improves the structural rigidity of the material, but also significantly enhances the chemical stability of the material under acidic conditions. The present invention greatly improves the adsorption performance of chitosan-based materials and the stability under acidic conditions, making it more practical.
[0026] The mass concentration of the formaldehyde solution of the present invention is 0.2% to 2%. When the concentration is lower than this, the occurrence of the cross-linking reaction will be reduced, resulting in a decrease in the degree of cross-linking of the material, thereby affecting its chemical stability under acidic conditions. On the contrary, when the concentration is higher, although the stability of the material is improved, a large number of active sites will be occupied by the cross-linking agent, making the structure too compact and reducing its specific surface area.
[0027] As a preferred technical solution of the present invention, the nitrogen-sulfur reagent includes thiourea, semicarbazide, guanylthiourea, phenylthiourea, acylthiourea, isothiourea, substituted thiourea, dimethylthiourea, 2-aminothiazole, 2-mercaptothiazole, 2-hydroxythiazole, 2-chlorothiazole, 2-carboxythiazole; any one of 2-amino-1,3,4-thiadiazole, 5-mercapto-1,3,4-thiadiazole, 2-carboxy-1,3,4-thiadiazole or 2,5-diamino-1,3,4-thiadiazole or a combination of at least two or more thereof.
[0028] Preferably, the nitrogen-sulfur reagent is any one of thiourea, semicarbazide or guanylthiourea.
[0029] In the present invention, any one of thiourea, semicarbazide or guanylthiourea is further selected because the sulfur and nitrogen groups have a strong affinity with gold ions and can quickly attract and capture gold ions during the adsorption process, thereby improving the adsorption efficiency and adsorption capacity.
[0030] As a preferred technical solution of the present invention, the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:(0.5-10), for example, it can be 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] The mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution in the present invention is 1:(0.5-10) because within this range, the reaction between the nitrogen-sulfur reagent and glutaraldehyde can be connected according to the molar ratio of the sulfur-nitrogen reagent to the aldehyde group of 1:2. If it is not within this range, the nitrogen-sulfur reagent and glutaraldehyde may react completely or incompletely. For example, if the nitrogen-sulfur reagent and glutaraldehyde react completely, the nitrogen-sulfur reagent will undergo polymerization and cannot be grafted onto chitosan in subsequent reactions; if the nitrogen-sulfur reagent and glutaraldehyde do not react completely, glutaraldehyde will be excessive, causing chitosan to polymerize, resulting in the inability of the nitrogen-sulfur reagent to be completely grafted onto chitosan. Both lead to incomplete grafting, which affects the adsorption capacity and performance of the adsorbent.
[0032] Preferably, the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 40°C to 90°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] The mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution in the present invention is 40° C. to 90° C. because within this range, the reaction can proceed at an appropriate rate while ensuring the completeness of the grafting reaction. If it is not within this range, the reaction rate may be too slow, resulting in incomplete connection between the nitrogen-sulfur reagent and glutaraldehyde, and the nitrogen-sulfur reagent cannot be completely grafted onto chitosan in the subsequent reaction, or the temperature is too high to induce a side reaction, causing the nitrogen-sulfur reagent to undergo a polymerization reaction, and the nitrogen-sulfur reagent cannot be completely grafted onto chitosan in the subsequent reaction. Both of these lead to incomplete grafting, which affects the adsorption capacity and performance of the adsorbent.
[0034] Preferably, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 2 h to 12 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the stirring speed of the mixture of the nitrogen-sulfur reagent and the glutaraldehyde solution is 200 r / min to 900 r / min, for example, it can be 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] As a preferred technical solution of the present invention, in step (3), the mass ratio of the first base solution to the second base solution is 1:(1-5), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] The mass ratio of the first base solution to the second base solution in the present invention is 1:(1-5) because within this range, the nitrogen-sulfur reagent can react completely with chitosan, graft the nitrogen-sulfur reagent onto chitosan, and increase the active sites of the adsorbent as much as possible. If it is not within this range, it may cause incomplete grafting of the nitrogen-sulfur reagent. If it is excessive, it will cause incomplete grafting and waste reagents. Conversely, a smaller amount will lead to incomplete grafting, a smaller number of active sites, and affect the adsorption capacity.
[0038] As a preferred technical solution of the present invention, in step (3), the emulsion is a mixture of liquid paraffin and span80.
[0039] It should be noted that the liquid paraffin and span 80 in the present invention are well known to those skilled in the art, and those skilled in the art can adaptively adjust the addition ratio of liquid paraffin and span 80 according to actual conditions. Among them, the addition ratio of liquid paraffin and span 80 can be 30: (1-5).
[0040] Preferably, in step (3), the cross-linking agent includes any one of formaldehyde, epichlorohydrin, glyoxal, citric acid or polyphosphoric acid, or a combination of at least two or more thereof, and glyoxal is more preferably used.
[0041] In the present invention, glyoxal is further selected because it has better cross-linking efficiency and stability, can effectively form a strong covalent bond with the nitrogen-sulfur reagent, and at the same time, glyoxal has two aldehyde groups and a relatively short molecular chain. Glyoxal can connect the amino groups in the chitosan-nitrogen-sulfur reagent to form a network structure, so that the adsorbent has a porous structure and a higher specific surface area. On the one hand, the cross-linking degree and durability of the adsorbent are improved, and on the other hand, a network porous structure is formed by cross-linking, the specific surface area is increased, and the adsorption capacity is improved.
[0042] As a preferred technical solution of the present invention, in step (3), the amount of the cross-linking agent used is 1 mL to 20 mL.
[0043] The amount of the crosslinking agent used in the present invention is 1 mL to 20 mL, which is mainly used to adjust the crosslinking degree and molecular structure of the adsorbent material. Too much or too little crosslinking agent will affect the crosslinking degree of the adsorbent material, thereby affecting its adsorption performance.
[0044] Preferably, in step (3), the pH value of the solution is adjusted in the following manner:
[0045] The pH value of the solution was adjusted using an alkaline reagent.
[0046] Preferably, the alkaline agent includes any one of sodium hydroxide solution, potassium hydroxide solution or ammonia solution, or a combination of two or more thereof.
[0047] Preferably, the concentration of the alkaline agent is 2mol / L to 4mol / L, for example, it can be 2mol / L, 2.2mol / L, 2.4mol / L, 2.6mol / L, 2.8mol / L, 3mol / L, 3.2mol / L, 3.4mol / L, 3.6mol / L, 3.8mol / L, 4mol / L, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, after adjusting the pH value of the solution, the pH value of the reaction solution is 9 to 12, for example, 9, 9.5, 10, 10.5, 11, 11.5, 12, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] As a preferred technical solution of the present invention, in step (4), the solid-liquid separation is carried out in the following manner:
[0050] Use filter paper or filter membrane to separate the solid and liquid of the reaction solution.
[0051] Preferably, the thickness of the filter paper is 150μ5-160μm, for example, it can be 150μm, 152μm, 154μm, 156μm, 158μm, 160μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the pore size of the filter membrane is 2 μm to 3 μm, for example, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] It should be noted that, after the solid-liquid separation of the reaction solution in the present invention, the mixture can be poured into a filtering device and initially filtered to obtain a chitosan polymer. Next, the solid is rinsed with petroleum ether, ethanol and deionized water in sequence to remove the residual emulsion components. Subsequently, the rinsed solid particles are placed in an ultrasonic cleaner and ultrasonically cleaned with petroleum ether to further remove the attached emulsion.
[0054] As a preferred technical solution of the present invention, in step (4), the elution treatment is carried out using an acidic solution.
[0055] Preferably, the acidic solution is a hydrochloric acid solution.
[0056] Preferably, in step (4), the concentration of the hydrochloric acid solution is 1 mol / L to 5 mol / L, for example, it can be 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, in step (4), the elution time is 12 h to 24 h, for example, it can be 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] The elution time in the present invention is 12h to 24h because within this range, the protected amino groups on the chitosan are fully eluted from the cross-linked structure, thereby avoiding excessive cross-linking of the amino groups or residual amino groups in the adsorbent, ensuring its subsequent availability and adsorption performance. If it is not within this range, it may cause incomplete or excessive elution of the amino groups, affecting the stability of the cross-linked structure, thereby reducing the adsorption efficiency and reusability of the adsorbent. Preferably, in step (4), the filtration treatment time is 10min to 30min, for example, it can be 10min, 12min, 14min, 16min, 18min, 20min, 22min, 24min, 26min, 28min, 30min, etc., but is not limited to the listed values, and other values not listed within this numerical range are also applicable.
[0059] Preferably, in step (4), the drying time is 12 h to 24 h, for example, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] Preferably, in step (4), the temperature of the drying treatment is 35°C to 70°C, for example, it can be 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] The temperature of the drying treatment described in the present invention is 35°C to 70°C because within this range, the moisture in the sample can be effectively removed while avoiding the damage to the material structure and chemical composition caused by excessively high temperatures. If it is not within this range, the moisture may not be completely removed when the temperature is too low, affecting the drying effect and further affecting the adsorption effect; while excessively high temperatures may cause excessive drying or thermal degradation of the material, reducing its adsorption performance.
[0062] As a preferred technical solution of the present invention, the preparation method specifically comprises:
[0063] (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution;
[0064] (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution;
[0065] (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution;
[0066] (4) The reaction solution in step (3) is subjected to solid-liquid separation, and the obtained solid particles are eluted in an acidic solution, and then filtered and dried in sequence to obtain a gold ion adsorbent.
[0067] in:
[0068] Step (1) and step (2) are performed in any order, the ratio between the mass of the chitosan powder and the volume of the acetic acid solution is 1 g: 4 mL to 5 mL, and the mass concentration of the formaldehyde solution is 0.2% to 2%;
[0069] The nitrogen-sulfur reagent includes thiourea, semicarbazide, guanylthiourea, phenylthiourea, acylthiourea, isothiourea, substituted thiourea, dimethylthiourea, 2-aminothiazole, 2-mercaptothiazole, 2-hydroxythiazole, 2-chlorothiazole, 2-carboxythiazole; any one of 2-amino-1,3,4-thiadiazole, 5-mercapto-1,3,4-thiadiazole, 2-carboxy-1,3,4-thiadiazole or 2,5-diamino-1,3,4-thiadiazole or a combination of at least two or more thereof.
[0070] The mass ratio of the nitrogen-sulfur reagent and the glutaraldehyde solution is 1:(0.5-10), the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 40°C-90°C, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 2h-12h, and the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 200r / min-900r / min.
[0071] The mass ratio of the first base solution to the second base solution is 1:(1-5).
[0072] The emulsion is a mixture of liquid paraffin and span80, the cross-linking agent includes any one of formaldehyde, epichlorohydrin, glyoxal, citric acid or polyphosphoric acid or a combination of at least two or more thereof, and the amount of the cross-linking agent used is 1 mL to 20 mL.
[0073] The pH value of the solution is adjusted as follows:
[0074] The pH value of the solution was adjusted using an alkaline reagent.
[0075] The alkaline reagent includes any one of sodium hydroxide solution, potassium hydroxide solution or ammonia solution or a combination of two or more thereof. The concentration of the alkaline reagent is 2 mol / L to 4 mol / L. After adjusting the pH value of the solution, the pH value of the reaction solution is 9 to 12.
[0076] The solid-liquid separation is carried out as follows:
[0077] Use filter paper or filter membrane to separate the solid and liquid of the reaction solution.
[0078] The thickness of the filter paper is 150 μm to 160 μm; the pore size of the filter membrane is 2 μm to 3 μm.
[0079] The acidic solution is a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 1 mol / L to 5 mol / L, the elution time is 12h to 24h, the filtration time is 10min to 30min, the drying time is 12h to 24h, and the drying temperature is 35°C to 70°C.
[0080] Illustratively, the separation and application method of the gold ion adsorbent prepared in the present invention may include the following steps:
[0081] The gold-containing material (gold ore or circuit board) is leached to obtain a gold-containing leaching solution, in which the gold ions are in the form of [AuCl4] - or [AuBr4] - Form exists;
[0082] The pH value of the leaching solution is adjusted, and the leaching solution is passed through an adsorption column filled with a gold ion adsorbent to adsorb and recover the gold ions.
[0083] The leaching agent used for leaching can be NCS or NBS, and the dosage thereof is 1kh / t to 10kg / t; the pH value is adjusted to 1 to 9, and the dosage of the adsorbent is 0.01g / L to 10g / L.
[0084] It should be noted that NCS in the present invention refers to N-chlorosuccinimide, and NBS refers to N-bromosuccinimide.
[0085] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0086] Compared with the prior art, the present invention has the following beneficial effects:
[0087] In the present invention, the -NH2 group in the glucosamine structural unit of chitosan is connected with active functional groups such as nitrogen and sulfur through the cross-linking effect of glutaraldehyde to form a macromolecular network structure. The adsorption of gold ions can be achieved through the coordination and complexation of sulfur atoms, amine groups and gold ions and redox as well as the electrostatic adsorption of protonated groups. The polymer can be used for extracting gold ions from ore gold leaching liquid and electronic waste. The overall preparation process is simple, easy to operate and low in cost, and the obtained adsorbent has high adsorption capacity and good selectivity. DETAILED DESCRIPTION
[0088] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0089] Example 1
[0090] This embodiment provides a method for preparing a gold ion adsorbent, comprising:
[0091] (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution;
[0092] (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution;
[0093] (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution;
[0094] (4) The reaction solution in step (3) is subjected to solid-liquid separation, and the obtained solid particles are sequentially subjected to elution treatment, filtration treatment and drying treatment to obtain a gold ion adsorbent.
[0095] in:
[0096] Step (1) and step (2) are performed in any order, the ratio between the mass of chitosan powder and the volume of acetic acid solution is 1 g:4 mL, and the mass concentration of formaldehyde solution is 0.4%.
[0097] The nitrogen-sulfur reagent is thiourea, the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:2, the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 40°C, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 12h, and the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 200r / min.
[0098] The mass ratio of the first base solution to the second base solution is 1:1.
[0099] The emulsion is a mixture of liquid paraffin and span80, the cross-linking agent is glyoxal, and the amount of the cross-linking agent used is 2 mL.
[0100] The pH value of the solution is adjusted in the following manner: an alkaline agent is used to adjust the pH value of the solution.
[0101] The alkaline reagent is a sodium hydroxide solution, and the concentration of the alkaline reagent is 2 mol / L. After adjusting the pH value of the solution, the pH value of the reaction solution is 9.
[0102] The solid-liquid separation is performed as follows: the reaction solution is subjected to solid-liquid separation using filter paper or filter membrane.
[0103] The thickness of the filter paper is 150 μm; the pore size of the filter membrane is 2 μm. The elution treatment is carried out with a hydrochloric acid solution with a concentration of 2 mol / L, the elution time is 14 h, the filtration time is 15 min, the drying time is 12 h, and the drying temperature is 70°C.
[0104] The gold ion adsorbent prepared in Example 1 is applied, wherein:
[0105] (1) From the collected waste CPU, a 3.0 cm × 3.0 cm sample was taken, the metal sheet was peeled off, and NBS was used for leaching for 24 h. 20 mL of the leaching solution was taken, 5 mg of gold ion adsorbent was added, the pH was adjusted to 2, and the adsorption time was 24 h. The element concentrations before and after adsorption and the adsorption recovery rates are shown in Table 1.
[0106] Table 1 Element concentration and adsorption recovery rate in CPU leachate before and after adsorption
[0107] element Initial concentration (ppm) Concentration after adsorption (ppm) Recovery rate (%) Cu 340.212 335.886 1.21 Ni 55.42 52.58 5.12 Pt 4.378 2.622 40.11 Au 2.147 0.019 99.12 Zn 1.547 1.535 0.75
[0108] It can be seen from Table 1 above that even in the presence of high concentration of Cu(II), the gold ion adsorbent prepared by the present invention still exhibits high selectivity and recovery rate for Au(III).
[0109] (2) Take 1 g of gold ore powder and use NBS solution to leach the gold ore powder for 24 h. Take 20 mL of leaching solution, add 3 mg of gold ion adsorbent, adjust the pH to 2, and adsorb for 24 h. The element concentrations before and after adsorption and the adsorption recovery rates are shown in Table 2.
[0110] Table 2 Element concentration and adsorption recovery rate in gold ore powder leaching solution before and after adsorption
[0111]
[0112]
[0113] Example 2
[0114] This embodiment provides a method for preparing a gold ion adsorbent, comprising:
[0115] (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution;
[0116] (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution;
[0117] (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution;
[0118] (4) The reaction solution in step (3) is subjected to solid-liquid separation, and the obtained solid particles are sequentially subjected to elution treatment, filtration treatment and drying treatment to obtain a gold ion adsorbent.
[0119] in:
[0120] Step (1) and step (2) are performed in any order, the ratio between the mass of chitosan powder and the volume of acetic acid solution is 1 g:4.5 mL, and the mass concentration of formaldehyde solution is 1%.
[0121] The nitrogen-sulfur reagent is thiosemicarbazide, the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:5, the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 70°C, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 8h, and the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 600r / min.
[0122] The mass ratio of the first base solution to the second base solution is 1:3.
[0123] The emulsion is a mixture of liquid paraffin and span80, the cross-linking agent is epichlorohydrin, and the amount of the cross-linking agent used is 10 mL.
[0124] The pH value of the solution is adjusted in the following manner: an alkaline agent is used to adjust the pH value of the solution.
[0125] The alkaline reagent is a potassium hydroxide solution, and the concentration of the alkaline reagent is 3 mol / L. After adjusting the pH value of the solution, the pH value of the reaction solution is 10.5.
[0126] The solid-liquid separation is performed as follows: the reaction solution is subjected to solid-liquid separation using filter paper or filter membrane.
[0127] The thickness of the filter paper is 154 μm; the pore size of the filter membrane is 2.5 μm.
[0128] The elution treatment was carried out using a hydrochloric acid solution with a concentration of 3.5 mol / L. The elution time was 17 h. The filtration treatment time was 10 min. The drying treatment time was 16 h. The drying treatment temperature was 50°C.
[0129] Example 3
[0130] This embodiment provides a method for preparing a gold ion adsorbent, comprising:
[0131] (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution;
[0132] (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution;
[0133] (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution;
[0134] (4) The reaction solution in step (3) is subjected to solid-liquid separation, and the obtained solid particles are sequentially subjected to elution treatment, filtration treatment and drying treatment to obtain a gold ion adsorbent.
[0135] in:
[0136] Step (1) and step (2) are performed in any order, the ratio between the mass of chitosan powder and the volume of acetic acid solution is 1 g:5 mL, and the mass concentration of formaldehyde solution is 2%.
[0137] The nitrogen-sulfur reagent is dimethylthiourea, the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:8, the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 90°C, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 3h, and the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 300r / min.
[0138] The mass ratio of the first base solution to the second base solution is 1:5.
[0139] The emulsion is a mixture of liquid paraffin and span80, the cross-linking agent is citric acid, and the amount of the cross-linking agent used is 13 mL.
[0140] The pH value of the solution is adjusted in the following manner: an alkaline agent is used to adjust the pH value of the solution.
[0141] The alkaline reagent is an ammonia solution, the concentration of the alkaline reagent is 4 mol / L, and after adjusting the pH value of the solution, the pH value of the reaction solution is 11.
[0142] The solid-liquid separation is performed as follows: the reaction solution is subjected to solid-liquid separation using filter paper or filter membrane.
[0143] The thickness of the filter paper is 160 μm; the pore size of the filter membrane is 3 μm. The elution treatment is carried out with a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 5 mol / L, the elution time is 12 h, the filtration treatment time is 18 min, the drying treatment time is 15 h, and the drying treatment temperature is 40°C.
[0144] Example 4
[0145] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the ratio between the mass of chitosan powder and the volume of acetic acid solution is 1:0.8, and other parameters and experimental conditions are the same as those in Example 1.
[0146] Example 5
[0147] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the ratio between the mass of chitosan powder and the volume of acetic acid solution is 1:7, and other parameters and experimental conditions are the same as those in Example 1.
[0148] Example 6
[0149] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:0.3, and the other parameters and experimental conditions are the same as those in Example 1.
[0150] Example 7
[0151] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:12, and the other parameters and experimental conditions are the same as those in Example 1.
[0152] Example 8
[0153] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the mass ratio of the first base solution to the second base solution is 1:0.8, and other parameters and experimental conditions are the same as those in Example 1.
[0154] Example 9
[0155] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the mass ratio of the first base solution to the second base solution is 1:6, and other parameters and experimental conditions are the same as those in Example 1.
[0156] Example 10
[0157] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the amount of the cross-linking agent used is 0.8 mL, and the other parameters and experimental conditions are the same as those in Example 1.
[0158] Embodiment 11
[0159] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the amount of the cross-linking agent used is 22 mL, and the other parameters and experimental conditions are the same as those in Example 1.
[0160] Example 12
[0161] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the concentration of the formaldehyde solution is 0.1%, and other parameters and test conditions are the same as those in Example 1.
[0162] Embodiment 13
[0163] This embodiment provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the concentration of the formaldehyde solution is 3%, and the other parameters and test conditions are the same as those in Example 1.
[0164] Comparative Example 1
[0165] This comparative example provides a method for preparing a gold ion adsorbent, which differs from Example 1 in that no formaldehyde solution is used, and other parameters and test conditions are the same as those of Example 1.
[0166] Comparative Example 2
[0167] This comparative example provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that no nitrogen-sulfur reagent is used, and other parameters and experimental conditions are the same as those in Example 1.
[0168] Comparative Example 3
[0169] This comparative example provides a method for preparing a gold ion adsorbent, which is different from Example 1 in that the first base solution and the second base solution are not mixed in the emulsion for post-treatment, and other parameters and experimental conditions are the same as those in Example 1.
[0170] The gold ion adsorbents in the above examples and comparative examples were tested for adsorption performance. The test method was to add the adsorbent to a 100 mg / L gold ion solution, and after 24 hours of reaction, the residual gold ion concentration in the solution was measured, and the recovery rate of the adsorbent for gold ions was calculated. The results are shown in Table 3 below.
[0171] Table 3 Test results of gold ion adsorbent
[0172]
[0173]
[0174] It can be seen from Table 3 that the performance of the gold ion adsorbent in the embodiment of the present invention is better than that of the gold ion adsorbent in the comparative example. This is because the present invention connects the -NH2 group in the glucosamine structural unit of chitosan with active functional groups such as nitrogen and sulfur through the cross-linking effect of glutaraldehyde to form a macromolecular network structure. The adsorption of gold ions can be achieved through the coordination and complexation of sulfur atoms, amine groups and gold ions and redox and the electrostatic adsorption of protonated groups. The polymer can be used for the extraction of gold ions in ore gold leaching solution and electronic waste. The overall preparation process is simple, easy to operate and low in cost, and the obtained adsorbent has high adsorption capacity and good selectivity.
[0175] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0176] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a gold ion adsorbent, characterized in that: The preparation method comprises: (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution; (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution; (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution; (4) subjecting the reaction solution in step (3) to solid-liquid separation, and subjecting the obtained solid particles to elution treatment, filtration treatment and drying treatment in sequence to obtain the gold ion adsorbent; There is no particular order in which steps (1) and (2) are performed.
2. The preparation method according to claim 1, characterized in that: The ratio between the mass of the chitosan powder and the volume of the acetic acid solution is 1 g: 4 mL to 5 mL; Preferably, the mass concentration of the formaldehyde solution is 0.2% to 2%.
3. The preparation method according to claim 1 or 2, characterized in that: The nitrogen-sulfur reagent includes thiourea, semicarbazide, guanylthiourea, phenylthiourea, acylthiourea, isothiourea, substituted thiourea, dimethylthiourea, 2-aminothiazole, 2-mercaptothiazole, 2-hydroxythiazole, 2-chlorothiazole, 2-carboxythiazole; any one of 2-amino-1,3,4-thiadiazole, 5-mercapto-1,3,4-thiadiazole, 2-carboxy-1,3,4-thiadiazole or 2,5-diamino-1,3,4-thiadiazole or a combination of at least two or more thereof; Preferably, the nitrogen-sulfur reagent is any one of thiourea, semicarbazide or guanylthiourea.
4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:(0.5-10); Preferably, the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 40° C. to 90° C.; Preferably, the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 2 h to 12 h; Preferably, the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 200 r / min to 900 r / min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (3), the mass ratio of the first base solution to the second base solution is 1:(1-5).
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), the emulsion is a mixture of liquid paraffin and span80; Preferably, in step (3), the cross-linking agent includes any one of formaldehyde, epichlorohydrin, glyoxal, citric acid or polyphosphoric acid, or a combination of at least two or more thereof, and glyoxal is more preferably used.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the amount of the cross-linking agent is 1 mL to 20 mL; Preferably, in step (3), the pH value of the solution is adjusted in the following manner: Use alkaline reagent to adjust the pH value of the solution; Preferably, the alkaline agent comprises any one or a combination of two or more of sodium hydroxide solution, potassium hydroxide solution or ammonia solution; Preferably, the concentration of the alkaline reagent is 2 mol / L to 4 mol / L; Preferably, after adjusting the pH value of the solution, the pH value of the reaction solution is 9-12.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (4), the solid-liquid separation is carried out as follows: Using filter paper or filter membrane to separate the reaction solution into solid and liquid; Preferably, the thickness of the filter paper is 150 μm to 160 μm; Preferably, the pore size of the filter membrane is 2 μm to 3 μm.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (4), the elution treatment is carried out using an acidic solution; Preferably, the acidic solution is a hydrochloric acid solution; Preferably, in step (4), the concentration of the hydrochloric acid solution is 1 mol / L to 5 mol / L; Preferably, in step (4), the elution time is 12h to 24h; Preferably, in step (4), the filtration treatment time is 10 min to 30 min; Preferably, in step (4), the drying time is 12h to 24h; Preferably, in step (4), the drying treatment temperature is 35°C to 70°C.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The preparation method specifically comprises: (1) dissolving chitosan powder in acetic acid solution, adding formaldehyde solution and stirring to obtain a first basic solution; (2) mixing and stirring the nitrogen-sulfur reagent and the glutaraldehyde solution to obtain a second basic solution; (3) mixing the first base solution in step (1) and the second base solution in step (2) in an emulsion, adding a crosslinking agent and adjusting the pH value of the solution to obtain a reaction solution; (4) performing solid-liquid separation on the reaction solution in step (3), eluting the obtained solid particles in an acidic solution, filtering and drying the solid particles in turn to obtain a gold ion adsorbent; in: Step (1) and step (2) are performed in any order, the ratio between the mass of the chitosan powder and the volume of the acetic acid solution is 1 g: 4 mL to 5 mL, and the mass concentration of the formaldehyde solution is 0.2% to 2%; The nitrogen-sulfur reagent includes thiourea, semicarbazide, guanylthiourea, phenylthiourea, acylthiourea, isothiourea, substituted thiourea, dimethylthiourea, 2-aminothiazole, 2-mercaptothiazole, 2-hydroxythiazole, 2-chlorothiazole, 2-carboxythiazole; any one of 2-amino-1,3,4-thiadiazole, 5-mercapto-1,3,4-thiadiazole, 2-carboxy-1,3,4-thiadiazole or 2,5-diamino-1,3,4-thiadiazole or a combination of at least two or more thereof; The mass ratio of the nitrogen-sulfur reagent to the glutaraldehyde solution is 1:(0.5-10), the mixing temperature of the nitrogen-sulfur reagent and the glutaraldehyde solution is 40° C.-90° C., the mixing time of the nitrogen-sulfur reagent and the glutaraldehyde solution is 2h-12h, and the stirring speed of the nitrogen-sulfur reagent and the glutaraldehyde solution is 200r / min-900r / min; The mass ratio of the first base solution to the second base solution is 1:(1-5); The emulsion is a mixture of liquid paraffin and span80, the cross-linking agent includes any one of formaldehyde, epichlorohydrin, glyoxal, citric acid or polyphosphoric acid or a combination of at least two or more thereof, and the amount of the cross-linking agent is 1 mL to 20 mL; The pH value of the solution is adjusted as follows: Use alkaline reagent to adjust the pH value of the solution; The alkaline reagent includes any one of sodium hydroxide solution, potassium hydroxide solution or ammonia solution or a combination of two or more thereof, the concentration of the alkaline reagent is 2 mol / L to 4 mol / L, and after adjusting the pH value of the solution, the pH value of the reaction solution is 9 to 12; The solid-liquid separation is carried out as follows: Using filter paper or filter membrane to separate the reaction solution into solid and liquid; The thickness of the filter paper is 150μm to 160μm, the pore size of the filter membrane is 2μm to 3μm; the acidic solution is a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 1mol / L to 5mol / L, the elution time is 12h to 24h, the filtration treatment time is 10min to 30min, the drying treatment time is 12h to 24h, and the drying treatment temperature is 35℃ to 70℃.